2012
DOI: 10.1002/hup.2240
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fluvoxamine levels and OCD symptoms/response in adult patients

Abstract: Objective In this study, we explored the possible relationships between plasma fluvoxamine levels and clinical features and/or response in adult obsessive–compulsive disorder (OCD) patients treated with this drug for 6 months. Methods Twenty OCD outpatients of both sexes who were already taking fluvoxamine (mean dose ± SD: 216.7 ±86.2) for at least 4 weeks were included in the study. The severity of OCD was assessed by means of the Yale–Brown obsessive–compulsive scale (Y‐BOCS). The fluvoxamine plasma levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, in two studies carried out by our research group, we noted better response of compulsive symptoms to either fluvoxamine or clomipramine in men than in women who suffer from obsessive-compulsive disorder 108 , 109 …”
Section: Pharmacodynamicsmentioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, in two studies carried out by our research group, we noted better response of compulsive symptoms to either fluvoxamine or clomipramine in men than in women who suffer from obsessive-compulsive disorder 108 , 109 …”
Section: Pharmacodynamicsmentioning
confidence: 66%
“…107 Interestingly, in two studies carried out by our research group, we noted better response of compulsive symptoms to either fluvoxamine or clomipramine in men than in women who suffer from obsessivecompulsive disorder. 108,109 Conclusions Both pharmacokinetic and pharmacodynamic differences between the sexes have been described that may influence psychotropic drug effects. Generally, women are characterized by lower levels of gastric acidity and lesser activity of some gastric enzymes, all of which are factors that increase drug plasma concentrations.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…A comparison of the present data with the TRR for adults with depression revealed that about half (51.4%) of all measured fluvoxamine concentrations were within the TRR for adults with depression, and almost one-third (31.4%) were above the TRR for adults. For OCD in adults, no TRR has been defined so far, as there are insufficient data on the topic [ 44 ]. In children and adolescents treated with fluvoxamine, a TRR has not yet been defined for any indication and no controlled TDM studies with fixed dose designs nor positron emission tomography (PET) studies to measure fluvoxamine concentration-serotonin transporter occupancy relationships are available.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Based on the fact that during the outbreak of the COVID-19 pandemic, it has a greater impact on patients with BD and newly diagnosed patients with BD caused by COVID-19, the current BD treatment remains difficult and the prognosis is still poor, and western medicine treatment inevitably has the disadvantages of large side effects, easy recurrence, and high cost. [ 23 ] Therefore, non-drug therapy and supplementary alternative drug therapy as adjuvant therapy are particularly important. In Eastern cultures, acupuncture has been used for thousands of years to treat a range of ailments, including mental disorders.…”
Section: Introductionmentioning
confidence: 99%